Doctrine of Hire and Fire in the Context of COVID-19 in India - A Critical Analysis - Chatterjee, Akash; Moitra, Moulinath; Bhattacharjee, Sagnik; Basu, Sayak; Mukherjee, Jaggik (International Journal of Law, Human Rights and Constitutional Studies; Vol 3 No 1 (2021): International Journal of Law, Human Rights and Constitutional Studies, 2021)
The plethora of labour legislations that we find today, enshrining the basic fundamental protection to the most crucial linchpin of any organisation or industry its labour force, stands rooted in the revolutionary philosophy that countered the growing capitalist disregard of workers in late 19 th Century. With social dynamism paving the path for a complete reversal of hierarchical supremacy in the world political order, the nature of industrial relations underwent a phenomenal transformation from an oppressive to a cooperative system. The paraphernalia of production emerged as a strong unit of labour solidarity that has till date shaped legislations on the subject of Labour. Researchers have closely analysed the prevailing pandemic with certain changes brought about in the labour scenario in the country. The study heavily relies upon doctrinal secondary data, combining an empirical approach in the form of collection of primary data by way of survey. The study is confined to India and expects in rendering a critical account.